2020
DOI: 10.1111/1467-9817.12303
|View full text |Cite
|
Sign up to set email alerts
|

The role of meta‐cognitive cues on the comprehension of proficient and poor readers

Abstract: We explored whether performance differences exist between proficient and poor readers on implicit text information. Next, we explored whether indices of meta‐cognitive monitoring predicted reading performance. Finally, we examined whether poor and proficient readers exhibited distinct meta‐cognitive profiles with respect to reading comprehension ability. Chilean undergraduate students (N = 146) completed a task on inconsistency detection within texts and a standardised reading comprehension performance measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…First, regardless of what types of strategies are taught, research supports the conclusion that teaching students strategies of any type improves critical learning outcomes such as metacomprehension accuracy (Griffin et al, 2008; Gutierrez & Schraw, 2015; Hacker et al, 2008; Soto et al, 2020; Thiede & Anderson, 2003; Thiede et al, 2005), especially in underperforming students (Bol et al, 2005; Gutierrez de Blume, 2017). Regarding level of learning strategy, research demonstrated that deep learning strategies are the most successful at improving learning and are more enduring than superficial strategies (Baeten et al, 2010; Dinsmore & Alexander, 2012; Struyven et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…First, regardless of what types of strategies are taught, research supports the conclusion that teaching students strategies of any type improves critical learning outcomes such as metacomprehension accuracy (Griffin et al, 2008; Gutierrez & Schraw, 2015; Hacker et al, 2008; Soto et al, 2020; Thiede & Anderson, 2003; Thiede et al, 2005), especially in underperforming students (Bol et al, 2005; Gutierrez de Blume, 2017). Regarding level of learning strategy, research demonstrated that deep learning strategies are the most successful at improving learning and are more enduring than superficial strategies (Baeten et al, 2010; Dinsmore & Alexander, 2012; Struyven et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…A series of studies has found that when students were explicitly instructed to use learning strategies, they were more likely to not only be engaged in the topic, but also to better regulate their learning process, and, consequently, improve learning outcomes. Hacker et al (2008), for example, reported positive effects for reflection, and Soto et al (2020) found that inferencing, as a metacognitive cue, improved learning and metacomprehension accuracy when explicitly taught to students. On a similar vein, several studies showed positive effects for learning and metacomprehension accuracy when students were trained in the use of specific strategies like rereading and summarizing (Griffin et al, 2008; Gutierrez & Schraw, 2015; Thiede & Anderson, 2003; Thiede et al, 2005).…”
Section: Theoretical Considerations: Self-regulated Learning and Meta...mentioning
confidence: 98%
“…The aforementioned studies mainly used calibration tasks (i.e., retrospective judgments of learning) to measure procedural metacognitive competences. Soto et al (2020) suggested that the performance in specific tasks that require monitoring, as it is required in an inconsistency task, might be more strongly associated with the achievement in reading comprehension than retrospective judgments of learning, which are used in calibration tasks.…”
Section: Discussionmentioning
confidence: 99%
“…By explicitly teaching students how vocabulary can be readily adapted across content areas, students can more easily access what they already know about the topic(s) from long‐term memory and infer deeper, more enriched meanings from information not included in the texts. Presumably, this enhances the reading comprehension skills of the students (Kintsch, 1988, 1998; Kintsch & Rawson, 2007; Soto et al, 2019; Soto, Gutierrez de Blume, Carrasco Bernal, & Contreras Castro, 2020) by connecting information across content areas. As research on factors that influence Lexile performance has shown, explicitly teaching strategies to improve reading comprehension, such as our own literacy across content approach, should enhance students' inferential skills (Soto et al, 2019).…”
Section: Discussionmentioning
confidence: 99%